Allylsilanes in the synthesis of three to seven membered rings: the silylcuprate strategy - Barbero, Asunción; Pulido, Francisco J.; Sañudo, M. Carmen (Beilstein Journal of Organic Chemistry, 2007)
Addition of low order phenyldimethylsilylcyanocuprates to allenes followed by "in situ" reaction of the intermediate silylcuprate with electrophiles ("the silylcuprate strategy") provides new routes for the synthesis of functionalised allylsilanes, which undergo highly stereocontrolled silicon-assisted intramolecular cyclizations leading to three to seven membered ring-formation.